Outcomes after emergency general surgery and trauma care in incarcerated individuals: An EAST multicenter study. Issue 1 (1st July 2022) - Bryant, Mary K.; Tatebe, Leah C.; Siva, Nandini Rajaram; Udekwu, Pascal O.; Wurzelmann, Mary; Crandall, Marie L.; Zuniga, Yohan Diaz; Tran, Virginia; Santos, Ariel; Krause, Cassandra; Turay, David; Nordham, Kristen D.; et al.
Abstract : Maine et al describe the first national look at surgical outcomes in incarcerated patients in this EAST Multi-center Study. How can we improve trauma and surgical care for this population? #EASTMulticenterStudy #Healthdisparities Abstract : BACKGROUND: The US incarcerates more individuals than any other country. Prisoners are the only population guaranteed health care by the US constitution, but little is known about their surgical needs. This multicenter study aimed to describe the acute care surgery (ACS) needs of incarcerated individuals. METHODS: Twelve centers prospectively identified incarcerated patients evaluated in their emergency department by the ACS service. Centers collected diagnosis, treatment, and complications from chart review. Patients were classified as either emergency general surgery (EGS) patients or trauma patients and their characteristics and outcomes were investigated. Poisson regression accounting for clustering by center was used to calculate the relative risk (RR) of readmission, representation within 90 days, and failure to follow-up as an outpatient within 90 days for each cohort. RESULTS: More than 12 months, ACS services evaluated 943 patients, 726 (80.3%) from jail, 156 (17.3%) from prison, and 22 (2.4%) from other facilities. Most were men (89.7%) with a median age of 35 years (interquartile range, 27–47). Trauma patients comprised 54.4% (n = 513) of the cohort. Admission rates were similar for trauma (61.5%) and EGS patients (60.2%). Head injuries and facial fractures were the most common injuries, while infections were the most common EGS diagnosis. Self-harm resulted in 102 trauma evaluations (19.9%). Self-inflicted injuries were associated with increased risk of readmission (RR, 4.3; 95% confidence interval, 3.02–6.13) and reevaluation within 90 days (RR, 4.96; 95% confidence interval, 3.07–8.01). CONCLUSION: Incarcerated patients who present with a range of trauma and EGS conditions frequently require admission, and follow-up after hospitalization was low at the treating center. Poor follow-up coupled with high rates of assault, self-harm, mental health, and substance use disorders highlight the vulnerability of this population. Hospital and correctional facility interventions are needed to decrease self-inflicted injuries and assaults while incarcerated. LEVEL OF EVIDENCE: Prognostic and epidemiological, Level III. Abstract :